DOUBLE ENTRY JOURNAL TECHNIQUE FOR THE STUDENTSâ READING COMPREHENSION - Amin, Bahrun (Lembaga Perpustakaan Unismuh Makassar, 2012)
The objective of the research is to know the improvement of the studentsâ reading comprehension using double entry journal technique at the second year studentsâ of SMA Neg. 1 Pasui. This research is a classroom action research consist of two cycles, the mean score of the studentsâ reading comprehension for diagnostic-Test is 5.95 which is categorized as poor classification. While the mean score of the studentsâ reading comprehension in cycle I was 6.39. It is higher than the studentsââ D-Test. But the result was still not significant, because it is still categorized as fair and under the KKM 60. So the research is continued to the cycle II and the mean score of the studentsâ reading comprehension of cycle II was 6.82. Having analyzed the data, it can be stated that the studentsâ reading comprehension at the second year in class XI of SMA Neg.1 Pasui is poor level before applying the double entry journal technique, but after applying the technique in the second cycle, the studentsâ reading comprehension is classified as good categories.Â Â Â Key words: Reading Comprehension, Double Entry Journal Technique.Tujuan dari penelitian ini adalah untuk mengetahui peningkatan pemahaman membaca siswa menggunakan teknik jurnal double entry pada siswa tahun kedua di SMA Neg. 1 Pasui. Penelitian ini merupakan penelitian tindakan kelas terdiri dari dua siklus, nilai rata-rata dari pemahaman membaca siswa untuk diagnostik-Test adalah 5.95 yang dikategorikan sebagai klasifikasi kurang. Sementara nilai rata-rata dari membaca pemahaman siswa pada siklus I adalah 6, 39. Ini lebih tinggi dari D-Test siswa. Tapi hasilnya masih belum signifikan, karena masih dikategorikan sebagai cukup dan di bawah KKM 60. Jadi penelitian dilanjutkan ke siklus II dan nilai rata-rata dari pemahaman membaca siswa dari siklus II adalah 6.82. Setelah menganalisis data, dapat dinyatakan bahwa pemahaman membaca siswa di tahun kedua pada kelas XI SMA Neg.1 Pasui adalah tingkatan kurang sebelum menerapkan teknik jurnal double entry, tapi setelah menerapkan teknik dalam siklus kedua, pemahaman membaca siswa diklasifikasikan sebagai kategori baik.Kata Kunci: Membaca Pemahaman, Double Masuk Journal Teknik.